Surface waves control bacterial attachment and formation of biofilms in thin layers - Hong, Sung-Ha (Sci Adv, 2020)
Formation of bacterial biofilms on solid surfaces within a fluid starts when bacteria attach to the substrate. Understanding environmental factors affecting the attachment and the early stages of the biofilm development will help develop methods of controlling the biofilm growth. Here, we show that biofilm formation is strongly affected by the flows in thin layers of bacterial suspensions controlled by surface waves. Deterministic wave patterns promote the growth of patterned biofilms, while wave-driven turbulent motion discourages patterned attachment of bacteria. Strong biofilms form under the wave antinodes, while inactive bacteria and passive particles settle under nodal points. By controlling the wavelength, its amplitude, and horizontal mobility of the wave patterns, one can shape the biofilm and either enhance the growth or discourage the formation of the biofilm. The results suggest that the deterministic wave-driven transport channels, rather than hydrodynamic forces acting on microorganisms, determine the preferred location for the bacterial attachment.